Regulatory Reform of Evidence Confiscation in Forestry Crimes for Sustainable Environmental Governance - R. Hendral R. Hendral; Anis Mashdurohatun; Permana Adi Kusumah; Fahmi Amrullah; Mahmoud Ismail (Contrarius Indonesia, 2026)
Regulations governing evidence confiscation in forestry crimes fail to ensure legal certainty and equitable protection, resulting in inconsistent enforcement and inadequate safeguards for indigenous peoples and forest dependent communities. This study analyzes the existing regulatory framework, identifies its normative weaknesses, and develops a regulatory reconstruction that strengthens legal certainty and justice in accordance with Article 28D paragraph (1) of the 1945 Constitution. The research adopts a constructivist paradigm and applies a socio legal approach to examine the relationship between legal norms and social realities. The study employs Justice Theory as the grand theory, Legal System Theory as the middle range theory, and Legal Protection Theory together with Progressive Law Theory as the applied theoretical framework. The findings demonstrate three principal results, first, the current legal framework fails to provide adequate legal remedies to challenge unlawful confiscation, establish compensation for wrongful seizures, impose accountability on officials who exceed their legal authority, and protect the customary rights of indigenous communities. Second, the existing regulatory framework contains significant deficiencies in post judgment objection procedures, the legal regulation of found timber utilization, and land management following state repossession, thereby undermining legal certainty and equitable protection. Third, the study proposes a comprehensive reconstruction of the Forestry Law, the Law on the Prevention and Eradication of Forest Destruction, and the relevant Presidential Regulation by introducing objection mechanisms, compensation provisions, procedural safeguards, and agrarian reform measures. These reforms establish a coherent and constitutionally consistent legal framework that strengthens legal certainty, enhances the protection of community rights, improves accountability in law enforcement, and supports sustainable forest governance.